Comprehensive Medical Support in Complex Emergencies (CMSCE): pilot course review - Quinn, John M; Jigar, Trisha; Reinwald, Michael; Annan, Percy S T; Aapore, Thomas; Wilson, James M; Bourdeaux, Margaret Ellis; Ulrichs, Timo; Bricknell, Martin Cm; Moore, Alan; Goebbels, Stefan; Haggenmiller, Christian (Globalization and health, 2022)
Global threats to health and health security are growing. Fragile and failed states, armed groups, ungoverned spaces, outbreaks and potential unknown "Disease X" threats, antimicrobial resistance (AMR), hybrid and gray zone conflict all exacerbate complex medical emergencies. These growing threats increase preventable morbidity and mortality of the most vulnerable populations. In an effort to promote best practices, standardize responses, and prevent excess death and disability in these contexts, The Kofi Annan International Peacekeeping Training Centre (KAIPTC), with support from multiple international partners and a volunteer facilitator faculty, administered the pilot course for military and civilian health officers involved in U.N. peacekeeping missions entitled, "Comprehensive Medical Support in Complex Emergencies (CMSCE 19)." This brief review paper provides a description of the process in designing and delivering an interdisciplinary course for providers and decision makers responding to complex emergencies. We conclude with best practices and next steps for course evolution.
Keywords: Humans; lidé; Emergencies; náhlé příhody